The Effect of Service Quality, Cargo Handling Rates, and Infrastructure Facilities on Customer Satisfaction in Aircraft Cargo Expedition Services Pt Angkasa Pura Logistik Yogyakarta - Praba, Hanasta; Mashudi, Mashudi (Riviera Publishing, 2024)
The demand for logistics services is currently high, evidenced by increased imports to Indonesia from 2022 to 2023. Logistics service providers, such as PT Angkasa Pura Logistik Yogyakarta, must consistently maintain customer satisfaction. Therefore, this study examines how service quality, pricing, and infrastructure influence customer satisfaction at PT Angkasa Pura Logistik Yogyakarta. This research investigates the impact of service quality, cargo handling tariffs, and infrastructure on customer satisfaction with air freight services provided by PT Angkasa Pura Logistik Yogyakarta. This study employs a quantitative approach, utilizing accidental sampling. The sample size consists of 80 respondents. Data analysis is conducted through multiple linear regression analysis (SPSS software version 26). The results indicate that service quality, cargo handling tariffs, and infrastructure positively and significantly impact customer satisfaction, both partially and simultaneously. The most significant variable influencing customer satisfaction is service quality.